2009
DOI: 10.4183/aeb.2009.437
|View full text |Cite
|
Sign up to set email alerts
|

sex difference and effects of gonadal hormones on thermal pain thershold in rat

Abstract: Various clinical and experimental studies indicate that gonadal hormones exert modulatory effects on nociception and analgesia.The aim of the present study was to investigate the role of gonadal hormones in the response by male and female rats to thermal nociceptive stimulation.Materials and Methods. 7 week old albino (Wistar) rats were used in our study. Animals were randomly divided into control, sham and ovariectomised or orchidectomised groups. Thermal pain threshold was measured through tail immersion tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…Previous experimental and clinical studies have confirmed a close relationship between sex steroids and pain modulation. (32,33,34). Neuropathic pain has been found more prevalent in women than in men in representative samples of general population (35,36).…”
Section: (Severe Neuropathy)mentioning
confidence: 98%
“…Previous experimental and clinical studies have confirmed a close relationship between sex steroids and pain modulation. (32,33,34). Neuropathic pain has been found more prevalent in women than in men in representative samples of general population (35,36).…”
Section: (Severe Neuropathy)mentioning
confidence: 98%